Role of VEGFB in electrical pulse stimulation inhibits apoptosis in C2C12 myotubes - Guo, LanLan; Li, YanJun; Xing, Zheng; Zhang, JingBo; Zhang, Jing (Peptides (New York, N.Y. : 1980), 2022)
Skeletal muscle is the major effector organ for exercise. It has been proposed that VEGFB is significantly related to apoptosis in various cell types but not yet in skeletal muscle. We hypothesize that the decrease of VEGFB in skeletal muscle participates in the occurrence of skeletal muscle apoptosis and that exercise inhibits apoptosis by elevating the expression of VEGFB in skeletal muscle cells. Based on this hypothesis, we developed in vitro experiments to mimic the effect of exercise through electrical pulse stimulation (EPS) to observe the effect of EPS on apoptosis and the change in VEGFB expression in differentiated myotubes. In addition, we employed RNA interference to explore whether VEGFB is directly involved in the regulation of myotube apoptosis during EPS. Our results showed that exogenous VEGFB167 significantly inhibited C2C12 myotube apoptosis induced by TNF-α treatment and that endogenous VEGFB in differentiated C2C12 myotubes was significantly upregulated by EPS. In addition, EPS significantly changed the expression of the apoptotic indicators Bax and Bcl-2 at the mRNA level and downregulated the protein expression of cleaved caspase-3. The antiapoptotic effect of EPS weakened substantially as VEGFB in C2C12 myotubes was inhibited. Taken together, these results indicate that exercise-like EPS inhibits apoptosis by increasing the expression of C2C12 myotube-derived VEGFB. •VEGFB inhibited C2C12 myotube apoptosis induced by TNF-α treatment.•VEGFB in C2C12 myotube was markly upregulated by EPS, meanwhile the apoptosis was significantly downregulated by EPS.•The antiapoptotic effect of EPS weakened as VEGFB was inhibited.